Randomised placebo-controlled study of the effect of paracetamol on asthma severity in adults. Issue 2 (12th February 2014) - Ioannides, Sally J; Williams, Mathew; Jefferies, Sarah; Perrin, Kyle; Weatherall, Mark; Siebers, Robert; Crane, Julian; Patel, Mitesh; Travers, Justin; Shirtcliffe, Philippa; Beasley, Richard
Abstract : Objective: To investigate the effect of regular paracetamol on bronchial hyper-responsiveness (BHR) and asthma control in adult asthma. Setting: Single research-based outpatient clinic. Participants: 94 adults with mild-to-moderate asthma received randomised treatment; 85 completed the study. Key inclusion criteria were age 18–65 years, forced expiratory volume in 1 s (FEV1 ) >70% predicted, provocation concentration of methacholine causing a 20% reduction in FEV1 (PC20 ) between 0.125 and 16 mg/mL. Key exclusion criteria included an asthma exacerbation within the previous 2 months, current regular use of paracetamol, use of high-dose aspirin or non-steroidal anti-inflammatory drugs, current or past cigarette smoking >10 pack-years. Interventions: In a 12-week randomised, double-blind, placebo-controlled, parallel-group study, participants received 12 weeks of 1 g paracetamol twice daily or placebo twice daily. Primary and secondary outcome measures: The primary outcome variable was BHR, measured as the PC20 at week 12. Secondary outcome variables included FEV1, fractional exhaled nitric oxide (FeNO) and asthma control questionnaire (ACQ) score. Results: At 12 weeks, the mean (SD) logarithm base two PC20 was 1.07 (2.36) in the control group (N=54) and 0.62 (2.09) in the paracetamol group (N=31). After controlling for baseline PC20, the mean difference (paracetamol minus placebo) was −0.48 doubling dose worsening in BHR in the paracetamol group (95% CI −1.28 to 0.32), p=0.24. There were no statistically significant differences (paracetamol minus placebo) in log FeNO (0.09 (95% CI −0.097 to 0.27)), FEV1 (−0.07 L (95% CI −0.15 to 0.01)) or ACQ score (−0.04 (95% CI −0.27 to 0.18)). Conclusions: There was no significant effect of paracetamol on BHR and asthma control in adults with mild-to-moderate asthma. However, the study findings are limited by low power and the upper confidence limits did not rule out clinically relevant adverse effects. Trial Registration: Australia New Zealand Clinical Trials Registry Number: NZCTR12609000551291.